Information technology in the service of modern education - Demianenko, T.; Kazmina, N. (My University, 2013)
The onrush of modern information technology attracting a new student’s generation interest, as well as the important tasks of the Ukrainian education reform determine the resolute adaptation of new technologies into the educational process. And it is the matter not only of Information Science as a branch of learning, but also of other academic disciplines, particularly foreign languages.
Keywords: modern education; technology; foreign languages